Radiographic Manifestations of Occupational Lung Disease. Issue 1 (January 2015) - Ahuja, Jitesh; Kanne, Jeffrey P.; Meyer, Cristopher A.
<x xml:space="preserve">Abstract</x> Occupational lung diseases comprise a wide group of disorders affecting airway, lung parenchyma, and pleura. These disorders result from accumulation of inhaled dust particles and chemicals. Occupational lung diseases can be acute or chronic and often there is long latency between the exposure and development of disease. Although silicosis, coal worker pneumoconiosis, and asbestos-related pleural and parenchymal diseases are becoming less common, hypersensitivity pneumonitis is increasingly recognized as an occupational lung disease. Occupational asthma is the most common occupational lung disease. A thorough occupational history along with imaging, particularly high-resolution computed tomography is extremely useful in diagnosing these diseases.